Examining How Macroeconomic Variables Influence Regional Autonomy: An Examination of Local Taxing Power - Faradina Zevaya; Manuel David Cruz; Fauzi Syafriel; Rita Purnama Sari; Ridho Syahputra (Pusbindiklatren Bappenas, 2024)
The Indonesian Central Government has granted local governments greater autonomy and authority in resource management, a process called decentralization. The impact of macroeconomic factors on regional autonomy in Jambi Province following fiscal decentralization explores how decentralization empowers local governments to optimize local income. The Financial Relations Law (UU HKPD) underscores the importance of local taxing Power for local administrations. Methodologically, this study utilizes panel data regression to investigate the influence of macroeconomic variables on regional autonomy. The qualitative analysis method is also employed to formulate policy strategies for enhancing local taxing Power. Results reveal some macroeconomic variables have a significant effect on regional autonomy. These are some recommendations to strengthen regional autonomy in Jambi Province, such as the identification of leading sectors regarding income tax, enhancement of supervision and law enforcement, taxpayer education, improvement of public service quality, the establishment of tax collection task forces, and innovation in tax administration.